Trace Element Geochemistry of Alluvial TiO2 Polymorphs as a Proxy for Sn and W Deposits - Gaspar, Miguel (2022)
The Segura mining field, the easternmost segment of the Góis–Panasqueira–Segura tin– tungsten metallogenic belt (north–central Portugal), includes Sn-W quartz veins and Li-Sn aplitepegmatites, which are believed to be genetically related to Variscan Granites. Sediment geochemistry indicates granite-related Ti-enrichments, locally disturbed by mineralization, suggesting magmatic and metamorphic/metasomatic titaniferous phases. Therefore, Segura alluvial samples and the geochemistry of their TiO2 polymorphs (rutile, anatase, and brookite) were investigated, and their potential as exploration tools for Sn and W deposits was evaluated. The heavy-mineral assemblages proved to be good proxies for bedrock geology, and TiO2 polymorph abundances were found to be suitable indicators of magmatic and/or metasomatic hydrothermal processes. The trace element geochemistry of Segura’s alluvial rutile, anatase, and brookite is highly variable, implying multiple sources and a diversity of mineral-forming processes. The main compositional differences between TiO2 polymorphs are related to intrinsic (structural) factors, and to the P-T-X extrinsic parameters of their forming environments. Anomalous enrichments, up to 9% Nb, 6% Sn andW, 3% Fe, 2% Ta, and 1% V in rutile, and up to 1.8% Fe, 1.7% Ta, 1.2% Nb, 1.1% W 0.5% Sn and V in anatase, were registered. Brookite usually has low trace element content (<0.5%), except for Fe (~1%). HFSE-rich and granitophile-rich rutile is most likely magmatic, forming in extremely differentiated melts, with Sn and W contents enabling the discrimination between Sn-dominant and W-dominant systems. Trace element geochemical distribution maps show pronounced negative Sn (rutile+anatase) and W (rutile) anomalies linked to hydrothermal cassiterite precipitation, as opposed to their hydrothermal alteration halos and toW-dominant cassiterite-free mineralized areas, where primary hydrothermal rutile shows enrichments similar to magmatic rutile. This contribution recognizes that trace element geochemistry of alluvial TiO2 polymorphs can be a robust, cost- and time-effective, exploration tool for Sn(W) and W(Sn) ore deposit systems.